Movement is Life—Optimizing Patient Access to Total Joint Arthroplasty: Chronic Kidney Disease Disparities. Issue 22 (15th November 2022) - Wiznia, Daniel H.; Nelson, Charles L.; Harrington, Melvyn
Abstract : Approximately 15% of the American adults have chronic kidney disease (CKD). Rates of CKD are higher in underserved communities: It is highest in African Americans (16%) and Hispanic individuals (14%). African Americans are more than 3 times as likely compared with their White counterparts to develop end-stage kidney disease, requiring dialysis or a kidney transplant. Rates of CKD are higher in the geriatric and socioeconomic disadvantaged populations, groups with higher rates of hip and knee osteoarthritis and with comorbidities, including obesity, diabetes mellitus, heart disease, and hypertension. CKD of any stage is associated with increased postoperative readmission, complications, and mortality. Patients on hemodialysis after total joint arthroplasty are at increased risk for complications, including periprosthetic joint infection, and given the reduction in risk after kidney transplant, there is varying opinion regarding whether patients on hemodialysis are safe arthroplasty candidates.